PENDEKATAN RASIONAL EMOTIVE BEHAVIOR THERAPY (REBT) ISLAMI DENGAN TERAPI AL-QUR'ĀN - Hasan, Wadhu Ali; Rahman, Imas Kania; Alim, Akhmad (FIKRAH, 2019)
This study aims to determine the effectiveness of the Islamic Rational Emotive Behavior Therapy (REBT) approach with al-Qur'ān therapy in reducing online game addiction. The design of this study was pre experiment with one group pretest-posttest design model. The participants of this study were grade XI vocational high school students who indicated online game addiction disorders, had low or high addiction level scores according to the size of the teenage level at the Geo Informatika Vocational School Bogor, which was Muslim. The level of addiction was measured using a Likert scale questionnaire number of 13 questions that have been tested for validity and reliability. The quantitative analysis test was conducted using the Microsoft Office Excel 2016 program, while the approach techniques in the form of observation, therapy and interviews were used to obtain additional qualitative data. Quantitative data were analyzed using paired sample t-tests. The results showed that there was a very significant difference in the level of online game addiction before and after being given therapy in the form of Islamic Rational Emotive Behavior Therapy (REBT) approach with a value of t = 3.26047 (p = 0.00087; p <0.05). The results of quantitative data analysis show that the Islamic Rational Emotive Behavior Therapy (REBT) approach with al-Qur'ān therapy can reduce the level of online game addiction.